2014
DOI: 10.1104/pp.114.243741
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Repression of Nuclear-Encoded Subunits of the Cytochrome b6f Complex in Tobacco Reveals an Extraordinarily Long Lifetime of the Complex    

Abstract: The biogenesis of the cytochrome b6f complex in tobacco (Nicotiana tabacum) seems to be restricted to young leaves, suggesting a high lifetime of the complex. To directly determine its lifetime, we employed an ethanol-inducible RNA interference (RNAi) approach targeted against the essential nuclear-encoded Rieske protein (PetC) and the small M subunit (PetM), whose function in higher plants is unknown. Young expanding leaves of both PetM and PetC  RNAi transformants bleached rapidly and developed necroses, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 79 publications
4
30
0
Order By: Relevance
“…Overall, the findings support the view that by contributing to R L during drought, AOX influences energy balance in the chloroplast, hence impacting both the PQ and NAD(P)H redox states. There is normally a strict co-regulation of the cyt b 6 f complex and ATP synthase amounts to balance the proton circuit, such that lumen acidification is sufficient to drive ATP synthesis, but without activating NPQ and photosynthetic control (Hojka et al 2014, Schöttler and. In WT tobacco, mild and moderate drought resulted in similar (and modest) declines in both cyt b 6 f and ATP synthase without generating any biochemical limitations of photosynthesis (Dahal et al 2015).…”
Section: Aox Impacts How the Photosynthetic Apparatus Acclimates To Dmentioning
confidence: 99%
“…Overall, the findings support the view that by contributing to R L during drought, AOX influences energy balance in the chloroplast, hence impacting both the PQ and NAD(P)H redox states. There is normally a strict co-regulation of the cyt b 6 f complex and ATP synthase amounts to balance the proton circuit, such that lumen acidification is sufficient to drive ATP synthesis, but without activating NPQ and photosynthetic control (Hojka et al 2014, Schöttler and. In WT tobacco, mild and moderate drought resulted in similar (and modest) declines in both cyt b 6 f and ATP synthase without generating any biochemical limitations of photosynthesis (Dahal et al 2015).…”
Section: Aox Impacts How the Photosynthetic Apparatus Acclimates To Dmentioning
confidence: 99%
“…Thus, it seems that regulation of the cytochrome b 6 f complex to halt electron transport (both linear and cyclic) may be a global strategy in different organisms and at different stress conditions. It was recently shown that in mature tobacco (Nicotiana tabacum) leaves, the cytochrome b 6 f complex has a rather long lifetime (Hojka et al, 2014). It is interesting, therefore, that this complex is targeted for degradation earlier than other proteins of the photosynthetic apparatus, which have considerably shorter lifetimes.…”
Section: Decline In Photosynthetic Activity and Protein Levelsmentioning
confidence: 99%
“…Another example of classic 2Fe-2S-containing protein is glutaredoxin (GRX), which has a similar role to FD (Rouhier, 2010). The 2Fe-2S cluster in Cyt b 6 f is bound to photosynthetic electron transfer C (PetC), a Rieske ironsulfur protein (Hojka et al, 2014). Among the three 4Fe-4S clusters in PSI, one of them is referred to as F X and is associated with the PsaA/PsaB (where Psa stands for PSI) heterodimer, while the other two are referred to as F A and F B and are bound to PsaC (Saenger et al, 2002;Golbeck, 2003;Amann et al, 2004;Lezhneva et al, 2004).…”
mentioning
confidence: 99%